Maternal and Offspring Sugar Consumption Increases Perigonadal Adipose Tissue Hypertrophy and Negatively Affects the Testis Histological Organization in Adult Rats - Córdoba-Sosa, Gabriela; Nicolás-Toledo, Leticia; Cervantes-Rodríguez, Margarita; Xelhuantzi-Arreguin, Nicté; Arteaga-Castañeda, María de Lourdes; Zambrano, Elena; Cuevas-Romero, Estela; Rodríguez-Antolín, Jorge (Frontiers in Cell and Developmental Biology, 2022)
Sugar intake has been associated with the development of male reproductive pathologies as a consequence of the increase and dysfunction in different adipose tissue depots. The establishment of these dysfunctions in the early stages of development is unknown. We evaluated the effect of maternal (pregnancy and lactation) and male offspring (from weaning to adulthood) consumption of 5% sucrose on perigonadal adipose tissue (PAT) and testis in adulthood. Two rat groups were compared, both including pregnant and lactating females: Control (C - drinking tap water) and sugar (S - consuming 5% sucrose solution). From weaning to adulthood with male offspring, four subgroups were formed: Control Mother →Control and Sugar offspring (CC, CS), Sugar Mother → Control, and Sugar offspring (SC, SS). At 120 postnatal days, the testes and PAT were collected and morphologically described. Furthermore, we quantified the number and cross-sectional-area of perigonadal adipocytes and their distribution. We found that the males from SC and SS groups showed high PAT weight (P˂0.005), a high number (P˂0.05), and a relative frequency of large adipocytes (P˂0.05). Establishing these results during gestational and lactation stages, and enhancing in adulthood due postnatal diet and its interaction. More macrophages, mast and Leydig cells were observed in the interstitial space of the testis for the CS, SC, and SS groups. Concluding that consumption of a high-carbohydrate maternal diet, program hypertrophy processes in adult PAT, developing and enhancing with sugar consumption during postnatal life. Furthermore, they are associated with inflammatory processes within the interstitial space of the testis